Introduction to sensors - Vetelino, John; Reghu, Aravind (CRC Press, Taylor & Francis Group, 2011)
Examines the theoretical foundations and practical applications of sensors in the modern era. This text explains various types of sensors, providing background on the development of each type to reveal the underlying rationale for its use.